In Vivo Attenuation of M-Current Suppression Impairs Consolidation of Object Recognition Memory - Kosenko, Anastasia (J Neurosci, 2020)
The M-current is a low voltage-activated potassium current generated by neuronal Kv7 channels. A prominent role of the M-current is to a create transient increase of neuronal excitability in response to neurotransmitters through the suppression of this current. Accordingly, M-current suppression is assumed to be involved in higher brain functions including learning and memory. However, there is little evidence supporting such a role to date. To address this gap, we examined behavioral tasks to assess learning and memory in homozygous Kv7.2 knock-in mice, Kv7.2(S559A), which show reduced M-current suppression while maintaining a normal basal M-current activity in neurons. We found that Kv7.2(S559A) mice had normal object location memory and contextual fear memory, but impaired long-term object recognition memory. Furthermore, short-term memory for object recognition was intact in Kv7.2(S559A) mice. The deficit in long-term object recognition memory was restored by the administration of a selective Kv7 channel inhibitor, XE991, when delivered during the memory consolidation phase. Lastly, c-Fos induction 2 h after training in Kv7.2(S559A) mice was normal in the hippocampus, which corresponds to intact object location memory, but was reduced in the perirhinal cortex, which corresponds to impaired long-term object recognition memory. Together, these results support the overall conclusion that M-current suppression is important for memory consolidation of specific types of memories. SIGNIFICANCE STATEMENT Dynamic regulation of neuronal excitation is a fundamental mechanism for information processing in the brain, which is mediated by changes in synaptic transmissions or by changes in ion channel activity. Some neurotransmitters can facilitate action potential firing by suppression of a low voltage-activated potassium current, M-current. We demonstrate that M-current suppression is critical for establishment of long-term object recognition memory, but is not required for establishment of hippocampus-dependent location memory or contextual memory. This study suggests that M-current suppression is important for stable encoding of specific types of memories.